Experimental Study of Temperature Distributions over the Heat Supply Object Surface Located at a Different Height in a Room with a Working Infrared Heater; AIP Conference Proceedings; Vol. 2337 : Thermophysical Basis of Energy Technologies (TBET 2020) - Voloshko I. V. Ivan (Technical thermal physics and nuclear energy, 2021)
Title screen